Time to Listen: Children’s Voice in Geoscience Education Research - Neenan, Emer Emily; Roche, Joseph; Bell, Laura (Frontiers in Environmental Science, 2021)
Arguably the greatest threat facing society is that posed by irreversible climate change. In tandem with mitigating the effects of climate change, we must now make decisions about issues such as renewable energy, sustainable and safe water supplies, management of renewable and non-renewable natural resources, and management of natural disasters. The current school-age generation will see the worst effects of climate change, including greater frequency and intensity of extreme weather events; shortages of water and other necessary resources; and dangers due to pollution and toxicity in human environments and the human food chain. The next generation is coming of age as difficult socio-political choices are being made at local and national levels to manage resources and mitigate environmental damage. It is therefore important to centre the voices of children and young people in research aiming to address the social, political, and educational dimensions of geoscience topics including climate change and related topics. This paper proposes the use of Children’s Research Advisory Groups (CRAGs) to meaningfully include children and young people as co-researchers in geoscience-related research.